2020
DOI: 10.1177/1178223420948477
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Breast Magnetic Resonance Imaging on Surgical Management in Symptomatic Patients With Invasive Lobular Carcinoma

Abstract: Objective: Due to an insidious proliferative pattern, invasive lobular breast cancer (ILC) often fails to form a defined radiological or palpable lesion and accurate diagnosis remains challenging. This study aimed to determine the value of preoperative magnetic resonance imaging (MRI) for ILC and its impact on surgical outcomes. Methods: Consecutive symptomatic patients diagnosed with ILC in a tertiary centre over a 9-year period were reviewed. The time from diagnosis until surgery, initial type of surgery/ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…28 A concern regarding preoperative breast MRIs is the potential for delaying definitive cancer treatment. 12,20 A potential reason for the low rate of preoperative breast MRI referrals may have been partly related to the concern of delays in surgical management. Delays are associated with both wait times to obtain the MRI and subsequent investigations of new suspicious findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 A concern regarding preoperative breast MRIs is the potential for delaying definitive cancer treatment. 12,20 A potential reason for the low rate of preoperative breast MRI referrals may have been partly related to the concern of delays in surgical management. Delays are associated with both wait times to obtain the MRI and subsequent investigations of new suspicious findings.…”
Section: Discussionmentioning
confidence: 99%
“…5,20,21 Delays associated with preoperative breast MRI are related to wait times to obtain the MRI and the time required for subsequent investigations, biopsy, and pathology results for new suspicious findings. Moloney et al 12,22 found that the time from diagnosis to surgery was 11.4 days longer when a preoperative MRI was performed for patients with ILC, while another study found no associated delay. In a study by Cordeiro et al, 20 factors contributing to surgical wait times were examined and they found that additional preoperative radiologic procedures, investigations, and biopsies prolonged wait times by 6 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to IDC which are usually well demarcated, ILC proliferation patterns are more typically diffuse with an irregular growth pattern and minimal desmoplastic reaction (24). Often, other than a slightly firm consistency, no mass may be identifiable clinically or radiologically until an advanced stage, due to the subtle insidious proliferative pattern of this subtype (25). Of the 5 cases of ILC, the Wavelia MBI system accurately identified all tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic challenges posed by ILC are well catalogued. 23–26 Having previously demonstrated the potential to detect this frequently occult histological subtype, 19 and now demonstrated promise in estimating its size and malignancy risk, the Wavelia system could potentially compliment modern practice and be of most benefit in the detection of these lobular cases.…”
Section: Discussionmentioning
confidence: 99%